Measuring labour market success: a comparison between immigrants and native-born Canadians using PIAAC - Annen, Silvia [Verfasser] (My University, 2019)
"Canadian society is characterised by a plurality of immigrants and Canadian migration policy and corresponding recognition approaches are strongly geared to economic criteria, qualifications and skills. This paper addresses the question how immigrants who have acquired their highest qualification outside Canada are able to use their foreign qualifications and skills in their current job. The analyses are conducted to verify the assumptions of human capital theory as well as the lack of transferability of human capital across country borders. To answer these questions a labour market success index is developed, which is used as a dependent variable in regression models. The results show that traditional operationalisations of human capital (years of education, years of work experience and skills) have a positive effect on individual labour market success. At the same time, being born abroad and having acquired one's highest qualification abroad in comparison to Canada, especially in a Non-Western country, has negative effects on the overall labour market success of an individual. Detailed comparisons regarding different indicators of labour market success also prove these comparatively negative effects. The results demonstrate the limited explanatory power of human capital theory and the necessity to complement it with Bourdieu's concepts of social and cultural capital." (author's abstract; BIBB-Doku)
OnlineFirst vom 15.5.2018
Keywords: G 1.2.3.1 Potenziale; P 1.7 Benachteiligte; G 1.3.3.1 Qualifikationsverwertung; I 2.3.2 Nordamerika; Einwanderer; Qualifikationsniveau; Berufliche Qualifikation; Auslandsqualifikation; Qualifikationsverwertung; Arbeitsmarkt; Kanada